Choledochal cyst type VI: a rare case report - Sangani, Viral G.; Pathak, Aasit L.; Patel, Bhupesh; Pugaliya, Aayushi (International Surgery Journal, 2024)
Choledochal cyst or biliary cyst is a congenital anomaly affecting the biliary tree. It involves the dilatation of the biliary tree that could affect the extra hepatic and/or the intrahepatic segments. We present a 40 year old female with constant right upper abdominal pain, diagnosed with choledochal cyst. She underwent laparoscopic cholecystectomy with choledochal cyst (CDC) excision. She was uneventful postoperatively and then discharged.